The Characteristics of Masculine Roles in Present-Day Lithuania - Kublickienė, Lilija (Sociologija. Mintis ir veiksmas, 2003)
The article analyses problems related to gender sociology. The main attention is focused on the importance of man’s studies, as the masculine aspect of gender issues is frequently given less attention than feminine problems. In Western countries, the importance of male studies is now being emphasised in particular. Three basic conceptual directions of investigation, which could be found in scientific sociological literature devoted for men and masculinism, could be pointed out. It is noted that currently scientific masculine researches that avoid one-sided ideological interpretation are more common. The concept of masculine studies could be defined as a very wide scope of investigation, which covers problems both caused and experienced by men. Still, systemic masculine studies are not numerous, and the need for them remains urgent. The article presents the results of an empirical study carried out in Lithuania; the findings of the study allow describing the criteria of masculinity that are currently dominant. In addition, the article attempts disclosing limitations faced by men when they aim to match the stereotypical roles attached to them. Filling of the present gap in the masculine studies would help to restore equality in the field of knowledge about both genders, which is particularly important in order to be better aware of specific problems of each gender and to initiate a constructive dialogue about both genders, which is particularly important in order to be better aware of specific problems of each gender and to initiate a constructive dialogue.